Grafting Of Autologous Non-Cultured Melanocytes For The Treatment Of Vitiligo : A Pilot Study - kumar Sudhir; Mishra Raj Kumar; Kumar Vijay; Singh A K (Indian Journal of Dermatology, 2003)
Vitiligo is a common, often heritable, acquired disorder. Although vitiligo does not cause any physical problem but it surely is a psychosocial disaster. Depigmented patches resistant to medical treatment need to be managed surgically. Surgically. Surgical procedures usually performed lead to unsatisfactory results and that too at the cost of scarring of normal donor site. Here we describe our experience with grafting of non-cultured autologous melanocytes, which is not associated with any scarring. We tried this method in 16 lesions in 8 patients of stable vitiligo. Due to its advantages, like no scarring at recipient sites, ability to re-pigment large area with small piece of skin graft, simplicity and feasibility in Indian conditions, this is a good alternative in the treatment of vitiligo.